Peptides-tethered vascular grafts enable blood vessel regeneration via endogenous cell recruitment and neovascularization - Wu, Yifan; Song, Lili; Shafiq, Muhammad; Ijima, Hiroyuki; Kim, Soo Hyun; Wei, Ran; Kong, Deling; Mo, Xiumei; Wang, Kai (Pergamon Press Ltd., 2023)
Cardiovascular injuries cause huge morbidity and mortality worldwide. Arterial reconstructions are generally performed either by using native grafts or synthetic grafts, both of which are limited by several complications. Synthetic biodegradable polymers offer a promising platform, which may also be modified to foster in situ tissue regeneration through the recruitment of host cells. Vascular endothelial growth factor (VEGF) promotes endo-thelialization and neovascularization in vascular grafts, however, an overdose of VEGF may induce tumor-like vasculature, which requires alternative strategies. The objective of this study was to exploit prominin-1-derived VEGF-binding peptide (BP) to improve neovascularization and endothelialization, while stromal cell -derived factor 1-alpha (SDF-1a) peptide to encourage endogenous stem/progenitor cells mobilization and complement BP-mediated vascular remodeling. The BP and SDF-1a peptides were covalently conjugated with low molecular weight poly (e-caprolactone) (LPCL) to afford LPCL-BP and LPCL-SDF-1a, respectively. Chemical analysis revealed successful modification of LPCL with peptides, which also displayed good cytocompatibility in vitro once blended along with high molecular weight PCL (HPCL). The bioactived vascular grafts were fabricated by blending LPCL-BP, LPCL-SDF-1a or dual peptide-polymer conjugates with HPCL. The in vivo tests of vascular grafts through rat abdominal aorta implantation model revealed that, compared with HPCL grafts, the dual peptides modified grafts exhibited superior patency and tissue regeneration at 4-week post-implantation, including stem cell recruitment, rapid endothelialization and functional SMC layer formation. Taken together, these results may have implications for the in situ regeneration of artificial blood vessels through the orches-tration of host's responses and endogenous cell recruitment.